Factors influencing employee retention: in a view of employee at Arkema Coating Resins (M) Sdn Bhd / Fadzreen Khalid - Khalid, Fadzreen (Faculty of Business and Management, 2018)
The purpose of this study is to determine the relationship between training and development, performance appraisal and welfare benefits towards employee retention in a view of employee at Arkema Coating Resins (M) Sdn Bhd. Arkema Coating Resins (M) Sdn Bhd is a manufacturing company located at Pasir Gudang Industrial Estate, Johor. The targeted population is 130 local employees of Arkema Coating Resins (M) Sdn Bhd and the sample in this study covered 92 respondents from the total population. The sample was selected through Simple Random Sampling (SRS) techniques. Data findings Frequency analysis shows that the top three highest frequencies were from Production Department with 46.7%, Quality Control & Technical Department with 13% and Maintenance Department with 10.9%. Next, the highest frequency of working experiences among those respondents were between 21 years to 24 years with 29.3% and then same percentage 27.2% for 6 years to 10 years and 11 years to 20 years. While the least was the respondent who works with Arkema below than 5 years. From Pearson Correlation analysis shows that only two independent variables which are performance appraisal and welfare benefits were significantly influence employee retention. Based on the regression models, the most influences variable among these three is welfare benefits with the highest Beta-value β = 0.234 then followed by performance appraisal and training and development. Plus, data findings indicate that only welfare benefits significantly influence employee retention with r = 0.270, p < 0.05 Therefore, this also results in only Hypothesis 3 is accepted.